Assessing the Reporting Quality of Mixed Methods Studies Addressing Racial and Ethnic Inequities Across the Cancer Control Continuum (2003–2022): A Methodological Review - P. Paul Chandanabhumma; Sinem Toraman Turk; Annika Agni; Kathryn Vanderboll; Sergi Fàbregues (International Journal of Qualitative Methods)
The aim of this article is to characterize the methodological features and appraise the reporting quality of mixed methods research studies on racial and ethnic health inequities across the cancer control continuum (i.e., cancer prevention, detection, diagnosis, treatment, survivorship, or a combination of these domains) in the United States. A methodological review of relevant peer-reviewed articles in public health and allied fields published from 2003 to 2022 was conducted to describe the research context, reported mixed methods components, and incorporation of community perspectives in these studies. We conducted a systematic search of the Ovid MEDLINE, Scopus, Web of Science, CINAHL, and PsycINFO databases to identify relevant studies, and synthesized the findings using qualitative content analysis. We found 49 articles reporting mixed methods studies that involved participants from diverse racial and ethnic groups across the United States. We found that the majority of the articles provided a justification for using mixed methods research and detailed the qualitative and quantitative methods used. However, we noted that a minor portion of the articles explained distinctive insights gained from integrating qualitative and quantitative findings or adequately incorporated the perspectives of communities impacted by health inequities. Utilizing and reporting mixed methods procedures and insights gained through collaborative efforts will optimize the value of mixed methods research in realizing health equity across the cancer control continuum. The findings of this review suggest opportunities to elaborate on key defining procedures of mixed methods research, engaging with community perspectives, and gaining distinctive insights from the approach.